Does Otovestibular Loss in the Autosomal Dominant Disorder DFNA9 Have an Impact of on Cognition? A Systematic Review - De Belder, Jonas; Matthysen, Stijn; Claes, Annes J.; Mertens, Griet; Van de Heyning, Paul; Van Rompaey, Vincent (Frontiers in Neuroscience, 2018)
Background and Purpose. Cognitive impairment has been observed in patients with bilateral vestibular loss (BVL) and in patients with sensorineural hearing loss (SNHL). DFNA9 is an autosomal dominant disorder that causes a combination of both sensory deficits by the 3rd to 5th decade. We therefore hypothesize a combined detrimental effect on cognition. The aim of this systematic review was to identify studies related to DFNA9 in general and its relationship with cognitive impairment more specifically. Materials and Methods. Several databases including Medline, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, ISI Web of Knowledge, and Web of Science were searched to accumulate information about DFNA9-mutations, including phenotype, genotype, pathophysiology, quality of life and imaging in general and cognitive function more specifically. A qualitative analysis was performed on the 55 articles that qualified. Results. The clinical features of DFNA9 are different along the 24 COCH mutations, described up to now. Vestibular symptoms generally present themselves a few years after SNHL onset in mutations associated with the vWFA-domain although they can precede SNHL onset in other mutations associated with the LCCL-domain. Quality of life (QoL) has not been studied extensively in DFNA9, although scarce work is available on the positive impact of cochlear implantation to rehabilitate hearing. No studies were found evaluating cognition in DNFA9 patients. Conclusion. Although cognitive impairment has been demonstrated in patients with hearing loss as well as in patients with bilateral vestibular loss, no studies have been reported on the combination of both sensory deficits, such as in DFNA9. Further research is warranted to correlate otovestibular status with cognition.